Pervivencia del mundo clásico en la literatura: tradición y relecturas - Stella Maris Moro (Humanitas Supplementum, 2017)
This volume presents a number of studies that project their interest on the ancient world and its permanence through the centuries. The authors gathered here construct a framework of approaches that reveal, from diverse points of view, the symbolic and expressive power of Greco-Latin Literature. In this sense, an inquiry questioning is proposed on the rewriting of classical texts and the intertextuality between myths and motives of the ancient literature in general and later dramaturgy. Each of the studies presented in this volume seeks to shed light on the reasons for the survival of these topics in criticism, literature and theatrical scene.